Respostas glicêmicas e insulinêmicas em equinos alimentados com aveia e coprodutos da agroindústria - Cardoso, Elaine Caroline (2011)
The glucose and insulin responses to a particular food are variable in horses due to chemical composition. This study aimed to compare the effect of time between the oats and the co-products of agribusiness on glucose and insulin responses in horses (at rest), after fasting for 12 hours and during the postprandial period. We used six experimental treatments consisting of oat grain, defatted rice bran, bran biscuit pellets, citrus pulp, soybean hulls and sunflower cake. The experimental design was a Latin square (6x6). Significant differences in glycemic response at 60, 90, 120, 180 and 240 minutes post-meal co-products of citrus pulp, soybean hulls and sunflower cake compared to oats. In insulin response, rice bran, soybean hulls and sunflower cake differ statistically from the oats at 90, 120, 180 and 240 minutes post-meal. The animals fed soybean hulls and sunflower cake presented lower glucose and insulin responses differing significantly from the responses obtained with oats. Rice bran and bran biscuits, within the time observed as compared with oats showed higher amount of glucose to the first thirty minutes post-meal and may be suitable for horses that require higher amounts of glucose quickly. Soybean hulls and sunflower cake because of the lower glucose and insulin responses compared with responses obtained with oats, may be an option for feeding horses on condition maintenance